ESX‐1 exploits type I IFN‐signalling to promote a regulatory macrophage phenotype refractory to IFNγ‐mediated autophagy and growth restriction of intracellular mycobacteria. (13th April 2016) - Lienard, Julia; Movert, Elin; Valfridsson, Christine; Sturegård, Erik; Carlsson, Fredric
Summary: The ability of macrophages to eradicate intracellular pathogens is normally greatly enhanced by IFNγ, a cytokine produced mainly after onset of adaptive immunity. However, adaptive immunity is unable to provide sterilizing immunity against mycobacteria, suggesting that mycobacteria have evolved virulence strategies to inhibit the bactericidal effect of IFNγ‐signalling in macrophages. Still, the host–pathogen interactions and cellular mechanisms responsible for this feature have remained elusive. We demonstrate that the ESX‐1 type VII secretion systems of Mycobacterium tuberculosis and Mycobacterium  marinum exploit type I IFN‐signalling to promote an IL‐12 low /IL‐10 high regulatory macrophage phenotype characterized by secretion of IL‐10, IL‐27 and IL‐6. This mechanism had no impact on intracellular growth in the absence of IFNγ but suppressed IFNγ‐mediated autophagy and growth restriction, indicating that the regulatory phenotype extends to function. The IFNγ‐refractory phenotype was partly mediated by IL‐27‐signalling, establishing functional relevance for this downstream cytokine. These findings identify a novel macrophage‐modulating function for the ESX‐1 secretion system that may contribute to suppress the efficacy of adaptive immunity and provide mechanistic insight into the antagonistic cross talk between type I IFNs and IFNγ in mycobacterial infection.